Out of the ordinary [large type] - Turano, Jen (Apart from the crowd, 2018)
Miss Gertrude Cadwalader hoped her position as the paid companion to Mrs. Davenport would be easy. But as she becomes acquainted with her employer, she realizes the wealthy Mrs. Davenport has a strange tendency to be a bit light-fingered with other people's trinkets. Gertrude is relieved when Mrs. Davenport decides to have a quiet summer away from the social scene--until the woman changes her mind in order to help a young socialite launch into society. When Gertrude is caught in the act of trying to return one of the trinkets by Mrs. Sinclair, the mother of shipping magnate Harrison Sinclair, the woman jumps to an unfortunate conclusion. Harrison is determined to mend fences with Miss Cadwalader, but he's unprepared for the escapades a friendship with her will entail.